2020
DOI: 10.32615/ps.2019.152
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and physiological responses of small seeded faba bean genotypes (Vicia faba L.) to salinity stress: identification of a contrasting pair towards salinity

Abstract: In this study, we examined the behavior of six faba bean (Vicia faba L.) genotypes under salinity conditions at the seedling stage. The evaluation was assessed using 21 morphological, physiological, and photosynthetic traits under control, moderate, and severe salinity conditions. The principal component analysis (PCA) was used to identify genotypes of contrasting behavior in response to salt stress and to characterize the important traits for salt tolerance. The result of PCA analysis showed that the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
2
9
0
1
Order By: Relevance
“…Eresen 87. Large genetic variation of faba bean in tolerance to salinity has also been reported in different studies 27 , 28 .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Eresen 87. Large genetic variation of faba bean in tolerance to salinity has also been reported in different studies 27 , 28 .…”
Section: Discussionsupporting
confidence: 61%
“…However, there are a few studies evaluating common parameters with this study. Rajhi et al 28 (2020) tested salinity (NaCl) resistance in six different bean genotypes. It was reported that mass of the fresh root, mass of fresh shoot, mass of total fresh plant, mass of the dry root, length of the root and length of the shoot parameters explained the phenotypic variance according to PCA 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study showed that tolerant cultivars of barley had gas-exchange traits unmodified or less affected under salinity stress [55]. Our results were also in agreement with those of Rajhi et al [56], who proved that photosynthetic capacity is an important trait for the plant to tolerate salt stress. Considering biomass and photosynthetic parameters, we could select pair genotypes with contradictory behavior to the combined stress salinity and hypoxia which is Najeh as tolerant and Saber as sensitive.…”
Section: Photosynthesis Does Not Limit Faba Bean Growth Under Stress ...supporting
confidence: 93%
“…Previous studies have gained widely insight into faba bean growth and productivity injured by salinity and drought stresses (Hashem et al, 2019;Rajhi et al 2020;Neji et al, 2021). The impact of biochar on mitigating the harmful effect of salinity and drought on plants was well studied (Hafeez et al, 2017;Rezaie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%